Awareness about breast feeding practices and vitamin A deficiency among mothers in Srikakulam district of Andhra Pradesh, South India - Sappati, Vasantha Rao; Krishnaiah, Sannapaneni; Sapur, Suneetha (International Journal Of Community Medicine And Public Health, 2021)
Background: To assess the awareness about breast feeding practices and to assess the knowledge, attitude and practice about the signs and symptoms of vitamin A deficiency (VAD) and vitamin A rich foods intake among mothers of children below 5 years in the Srikakulam district of Andhra Pradesh (AP) in South India. Methods: A population based cross-sectional study was conducted on 284 mothers (age range 14 to 36 years) during June 2011 and September 2011. A combined simple and systematic random sampling strategy was used to select mothers from one tribal, rural and semi urban area with a representative sample of the Srikakulam district. A standardized structured questionnaire that was developed and validated by the National institute of nutrition, Hyderabad was utilized for this study. Results: The awareness of vitamin A and night blindness was 68.7% (95% confidence intervals (CI): 62.9–74.0) (n=195) and 93.7% (95% CI: 90.2–96.2) (n=266) respectively. The knowledge of signs and symptoms of vitamin A deficiency (VAD) was nil among illiterate mothers and low among literates; with primary education, adjusted odds ratio (OR): 0.01 (95% CI: 0.00, 0.06) and with secondary education, OR: 0.19 (95% CI: 0.06, 0.62) compared to mothers with graduation and above. Conclusions: There is a need to increase the awareness and knowledge about VAD among mothers with children below 5 years in the southern state of AP.